Pengaruh Gaya Belajar terhadap Hasil Belajar Mahasiswa Pendidikan Ekonomi 2022 Universitas Negeri Medan - Meiriza, Mica Siar; Rezeki, Mentari; Safira, Vivi; Dwi, Vingky; 'Afifah, Zulfa; Manurung, Tasya (Ikatan Da'i Indonesia, 2024)
This research aims to determine the influence of learning styles on the learning outcomes of 2022 Economics Education students at Medan State University. The research method used is a quantitative method with the data collection technique used in the form of a questionnaire. The data analysis technique in this research uses simple regression and linearity tests. The results of the research show that there is no positive and significant influence between learning styles on the learning outcomes of 2022 Economic Education students at Medan State University